2012
DOI: 10.1039/c2dt12307j
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Ag@Fe3O4 core–shell nanospheres: fabrication, characterization and application as reusable nanocatalysts

Abstract: Superparamagnetic Ag@Fe(3)O(4) nanospheres with core-shell nanostructures have been prepared by a facile one-pot method. The diameter of the as-synthesized nanospheres was about 200 nm and the core sizes were between 50 and 100 nm. By varying the concentrations, particles with tunable core size and total size are successfully achieved. Time dependent experiments were constructed to investigate the synthesis mechanism, which indicated that the present method corresponded to an Ostwald ripening progress. The BET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…However, MNP ST , and MNP CS were found less agglomerated, which reveals that starch and casein capping can prevent the agglomeration of MNPs (Fig. (B,C)) . Further, we confirmed that the average size of the MNP ST and MNP CS were ∼7.1 and ∼9.0 nm respectively.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…However, MNP ST , and MNP CS were found less agglomerated, which reveals that starch and casein capping can prevent the agglomeration of MNPs (Fig. (B,C)) . Further, we confirmed that the average size of the MNP ST and MNP CS were ∼7.1 and ∼9.0 nm respectively.…”
Section: Resultssupporting
confidence: 59%
“…1(B,C)). 41 Further, we confirmed that the average size of the MNP ST and MNP CS were ∼7.1 and ∼9.0 nm respectively.…”
Section: Synthesis and Characterization Of Mnpssupporting
confidence: 66%
“…Fe 3 O 4 @Ag nanoparticles, reported by Xuan et al, took about 40 min for the catalytic reduction with a rate constant of 8 × 10 –4 s –1 62. Jiang et al have reported iron oxide@silver core–shell nanocomposite for the reduction, and the time taken is about 30 min 63. Zhu et al have reported the conversion of 4‐nitrophenol to 4‐aminophenol in 4 min using Fe 2 O 3 @C@silver core–shell nanostructures, and the rate constant was found to be 1.03 min –1 25.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure (d), EDS demonstrated that Fe 3 O 4 contained more Fe and less C. The Fe signal consisted of the characteristic peaks of the magnetite nanoparticles, and the less intense C signal might originate from the carbon‐coated copper grid . The N signal as shown in Figure (e,f) was assigned to the graft monomer (AM), which proved that the polymer shell was successfully coated on the surface of the Fe 3 O 4 nanoparticles .…”
Section: Resultsmentioning
confidence: 83%